Enhancing sustainability in irrigation networks: A multicriteria method for optimizing flow distribution and reducing environmental impact - Melvin Alfonso Garcia-Espinal; Francisco-Javier Sanchez-Romero; Modesto Perez-Sanchez; P. Amparo Lopez-Jimenez (Results in Engineering, 2024)
Irrigation systems significantly enhance agricultural productivity but are also substantial consumers of water, energy, and natural resources. The need to optimize their design encouraged agronomic engineering to develop various methods for improving the design and management of these irrigation networks. This development focuses on creating a tool to define the optimal flow distribution according to the system's irrigation or consumption needs, thereby determining the design flows. The aim is to optimize the design of pipe diameters to improve sustainability (i.e., reducing CO2 emissions, minimizing service pressure, and maximizing recoverable energy within the system). These principles ensure a better evaluation of sustainable development goals within agricultural production. The proposed procedure develops a strategy to define the best-fitting distribution using a multicriteria solution. As novel, the research develops a tool, which characterizes flow distributions deviating from the classic Clement's formulation used in irrigation systems. The proposed method was applied in a Mediterranean irrigation system in Spain, achieving a correlation coefficient above 0.9 in the model. This methodology addresses design criteria in terms of sustainability and reduces energy consumption in networks. It achieved material savings of 6.01 % compared to the observed network, reducing CO2 emissions between 5.61 and 5.72 TnCO2/ha over its lifecycle.